New Construction Weighted (h,q)-Genocchi Numbers and Polynomials Related to Zeta Type Functions - Serkan Araci; Jong Jin Seo; Dilek Erdal (Discrete Dynamics in Nature and Society)
The fundamental aim of this paper is to construct (h,q)-Genocchi numbers and polynomials with weight α. We shall obtain some interesting relations by using p-adic q-integral on Zp in the sense of fermionic. Also, we shall derive the (h,q)-extensions of zeta type functions with weight α from the Mellin transformation of this generating function which interpolates the (h,q)-Genocchi numbers and polynomials with weight α at negative integers.